Influence of the situational variables on the performance of the teams competing in the Chinese Super League - Jiménez, S. L.; Bustamante-Sánches, Á.; Kelly, A. L.; Pareja-Galeano, H.; Lago-Penas, C. (International Journal of Performance Analysis in Sport, 2022)
The aim of this study was to assess the impact of situational variables, match location, quality of the opponent, and final result on the performance of the teams during an entire season (2016) of the Chinese Super League throughout 474 matches. Results showed that playing as an away team reduced the number of positional attacks per game, total ball possession time, possession in the final third of the field, possession in opponent half, passes attempted, passes accurate, crosses, passes forward, picking up free balls, and picking up free balls in opponent half. Final result only affected total attacks made per game and lost ball by the teams that finished the season between the 8th and the 16th position. These teams made an average of 99.29 attacks per game, which was lowered by 1.53 attacks for each goal that the team had in comparison with the opponent at the end of the match. In addition, number of lost balls was also reduced by 1.49 per game for each goal that one team had in comparison with the opponent at the end of the match. Overall, combinations of these variables could be used in order to predict the performance of soccer teams.